2023
DOI: 10.1186/s12944-023-01946-5
|View full text |Cite
|
Sign up to set email alerts
|

Association between total cholesterol and lumbar bone density in Chinese: a study of physical examination data from 2018 to 2023

Yongbing Sun,
Xin Qi,
Xinbei Lin
et al.

Abstract: Background The impact of total cholesterol (TC) on lumbar bone mineral density (BMD) is a topic of interest. However, empirical evidence on this association from demographic surveys conducted in China is lacking. Therefore, this study aimed to examine the relationship between serum TC and lumbar BMD in a sample of 20,544 Chinese adults between the ages of 20 and 80 years over a period of 5 years, from February 2018 to February 2023. Thus, we investigated the effect of serum TC level on lumbar B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Previous studies have shown that higher ALP levels are positively associated with low BMD or osteoporosis, which is consistent with the conclusions we have drawn, probably because alkaline phosphatase activity is increased when skeletal disease is present to meet the demands of bone growth and reconstruction ( 40 , 41 ). There is no clear consensus on the relationship between total cholesterol and BMD, and most studies agree with us ( 42 – 44 ) that there is a negative correlation between the two, however, there are also studies that take the opposite view ( 40 ), and a cross-sectional study from China found that the associations were very different in men and women, with TC positively correlated with BMD in men and In women, the association was U-shaped, with curve inflection points varying by age and BMI ( 45 ). Therefore, the association and mechanisms between TC and BMD need to be explored in further studies.…”
Section: Discussionmentioning
confidence: 54%
“…Previous studies have shown that higher ALP levels are positively associated with low BMD or osteoporosis, which is consistent with the conclusions we have drawn, probably because alkaline phosphatase activity is increased when skeletal disease is present to meet the demands of bone growth and reconstruction ( 40 , 41 ). There is no clear consensus on the relationship between total cholesterol and BMD, and most studies agree with us ( 42 – 44 ) that there is a negative correlation between the two, however, there are also studies that take the opposite view ( 40 ), and a cross-sectional study from China found that the associations were very different in men and women, with TC positively correlated with BMD in men and In women, the association was U-shaped, with curve inflection points varying by age and BMI ( 45 ). Therefore, the association and mechanisms between TC and BMD need to be explored in further studies.…”
Section: Discussionmentioning
confidence: 54%
“…In subgroup analyses, we found that the inverse association between TC levels and lumbar BMD was more pronounced in women and Mexican Americans, underscoring the importance of tailored interventions. However, a study conducted in China found that serum TC was positively correlated with lumbar BMD in men, while a U-shaped correlation was observed between serum TC and lumbar BMD in women [31]. The differences in study results may be related to the different study populations and covariates used.…”
Section: Discussionmentioning
confidence: 91%